2019
DOI: 10.3727/096504018x15399945637736
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Exerts Anticancer Effect in Nasopharyngeal Carcinoma In Vitro and In Vivo

Abstract: Baicalein, an active ingredient separated from Astragalus membranaceus, has shown its anticancer ability in various cancers. However, its effect on nasopharyngeal carcinoma has not been explored yet. The present study aimed to investigate the effect of baicalein on the growth, proliferation, apoptosis, and cell cycle of human nasopharyngeal carcinoma cells, as well as transplanted nude mouse xenograft. The results showed that baicalein inhibited the growth and proliferation of CNE1 and CNE2 cells in a time- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The application of baicalein, as a main bioactive ingredient extracted from the root of medical herb Scutellaria baicalensis , has been studied in the treatment of a variety of cancers, such as breast cancer, NSCLC, nasopharyngeal carcinoma, hepatocellular carcinoma, and the underlying mechanisms mainly focus on inducing apoptosis and autophagy, cell cycle arrest, inhibiting proliferation and invasion of tumor cells ( Bie et al, 2017 ; Yan et al, 2018 ; Guo et al, 2019 ; Nik Salleh et al, 2020 ; Zhang et al, 2020 ). In addition to malignant cells, increasing evidence demonstrated the dominant role of the large proportions of immune cells within the TME in orchestrating tumor progression and resistance to anti-tumor drugs ( Cassetta and Pollard, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of baicalein, as a main bioactive ingredient extracted from the root of medical herb Scutellaria baicalensis , has been studied in the treatment of a variety of cancers, such as breast cancer, NSCLC, nasopharyngeal carcinoma, hepatocellular carcinoma, and the underlying mechanisms mainly focus on inducing apoptosis and autophagy, cell cycle arrest, inhibiting proliferation and invasion of tumor cells ( Bie et al, 2017 ; Yan et al, 2018 ; Guo et al, 2019 ; Nik Salleh et al, 2020 ; Zhang et al, 2020 ). In addition to malignant cells, increasing evidence demonstrated the dominant role of the large proportions of immune cells within the TME in orchestrating tumor progression and resistance to anti-tumor drugs ( Cassetta and Pollard, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein, a flavonoid compound from dry roots of S. baicalensis, has anticancer activities both in vitro and in vivo. Baicalein exerted inhibitory effects on cell growth and cell cycle of numerous cancers through various molecular pathways such as PI3K/Akt [31], Wnt/β-catenin [27], and caveolin-1/AKT/mTOR [24], and the upregulation of p53 and caspases [22]. A previous study on NPC with baicalein showed that a decrease in cell viability of an EBV-positive NPC cell line was mediated through the downregulation of transcription factor specificity protein 1 (Sp1) and reduction in the EBNA1 activity in a doseand time-dependent manner [25].…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein is one of the major bioactive flavonoids predominantly found in dried roots of the traditional herb Scutellaria baicalensis, Georgi [15]. It has various biological activities, including antiviral, antibacterial, anti-thrombotic, antidiabetic, anti-inflammation, and anticancer activities [16][17][18][19][20][21][22]. In addition, baicalein inhibits various types of cancers through distinct cellular signaling pathways [15,[21][22][23][24][25][26][27]].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations